2006
DOI: 10.1021/jf060720a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effect of Quercetin and Its Equimolar Mixtures with Phenyltin Compounds on Liposome Membranes

Abstract: Our earlier studies have shown that the compounds diphenyltin dichloride (DPhT) and triphenyltin chloride (TPhT) in the presence of UVC radiation enhanced the degree of phosphatidylcholine liposome membrane oxidation (J. Agric. Food Chem. 2005, 53, 76-83). The prooxidative behavior of the compounds has now been confirmed with the electron paramagnetic resonance method, which proved the possibility that the studied compounds can exist in free radical forms. The present work investigates the possibility of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 54 publications
7
15
0
3
Order By: Relevance
“…The metal complexes used in the study showed good activities as a radical scavenger compared to the scavenging ability of ascorbic acid, which was used as a standard (Figure 5). These results were in agreement with previous studies of metallic complexes [32, 33] in which the ligand has antioxidant activity and it is expected that the metal moiety will increase its activity.…”
Section: Resultssupporting
confidence: 93%
“…The metal complexes used in the study showed good activities as a radical scavenger compared to the scavenging ability of ascorbic acid, which was used as a standard (Figure 5). These results were in agreement with previous studies of metallic complexes [32, 33] in which the ligand has antioxidant activity and it is expected that the metal moiety will increase its activity.…”
Section: Resultssupporting
confidence: 93%
“…The metal complexes showed good activities as a radical scavenger compared with ascorbic acid, Figure 9. These results were in agreement with previous metallic complexes studies where the ligand has the antioxidant activity and it is expected that the metal moiety will increase its activity [44,45,46]. …”
Section: Resultssupporting
confidence: 93%
“…There are literature reports of metallic complexes where the ligand has antioxidant activity and it is expected that the metal moiety will increase its activity [26,29,44,45,46]. In this case, the three heterocarboxylic acid isomers show a moderated antioxidant activity even though, their use in diverse applications has been reported, for example, ligand II is an antihyperlipidemic drug and its widely used in patients with atherosclerosis [47]; also for ligand III , some authors refer its wide biological applications but these do not include antioxidant activity [48].…”
Section: Resultsmentioning
confidence: 99%
“…Gabrielska et al . [29] found that the addition of Ph 2 SnCl 2 to quercetin increased its antioxidant activity. In our research, ligand II did show a moderate antioxidant activity towards the DPPH stable free radical, but the complex derived from this ligand and Ph 2 SnCl 2 (Figure 2, compound 5 ) did show a high percentage of scavenging activity (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation